MODERNISASI PESANTREN MELALUI DIGITALISASI: ANALISIS PENGGUNAAN FINGERPRINT, ID CARD, DAN PENILAIAN AMAL SHALIH DI MARYAM COLLAGE - Muhammad Efsal Syaputra; Rusmin Rusmin; Nur Arfiyyah Azzahra; Faturrohim Faturrohim; Tatia Ramadhani (J-MD Jurnal Manajemen Dakwah, 2025)
This study examines the digitalization process implemented at Maryam Collage, a modern Islamic boarding school that strives to integrate technology with Islamic values in its daily educational activities. The research is grounded in the central question of how digital-based systems such as the amal shalih performance assessment, fingerprint and ID card attendance systems, and digital data management contribute to improving students’ discipline, administrative efficiency, and institutional effectiveness. This study positions itself to fill the existing gap in literature regarding digital transformation within Islamic boarding schools that maintain strong moral and spiritual frameworks. Using a qualitative descriptive approach through in-depth interviews, direct observation, and documentation, the study provides a contextual understanding of how digitalization is implemented within the institution. The results indicate that the digital system has significantly enhanced the accuracy of activity recording, transparency in evaluation, and the speed of decision-making processes. The amal shalih assessment system is shown to strengthen students’ motivation and positive behavior, while the use of social media contributes to improving the institution’s public image and outreach. Despite technical challenges such as limited devices, unstable internet connectivity, and gradual user adaptation, the overall digitalization process proves to be a strategic step in building an Islamic educational institution that is modern, efficient, and competitive without losing its spiritual identity. Consequently, this research provides an important contribution to the study of digital transformation in Islamic boarding schools and highlights the potential of technology-based educational systems that remain rooted in spiritual values.